British evangelical missions to Spain in the nineteenth century - Sitoy, T. Valentino S. (The University of Edinburgh, 1972)
It was in Spain that the sixteenth-century Protestant Reformation suffered a complete defeat. For more than two centuries, that country was sealed from further incursions of the Reformed Faith, owing to the vigilance of the Inquisition and the zeal of her monarchs in preserving her Catholic unity. She nineteenth century, however, unleashed forces which brought about revolutionary changes in Spain, and made possible that Protestant missionary enterprise, which came to be known as 'Spanish evangelization'. The introductory chapter of this thesis prepares the setting for this particular endeavour, and attempts to explain why certain circles of British evangelical Protestants exerted efforts for the 'evangelization' of Spain.

Protestantism came to Spain at this time in the wake of political liberalism, so that in the minds of many Spaniards, the two were but different sides of the same coin. She second chapter deals with the early attempts of a few British evangelical societies to enter Spain during liberal periods between 1800 and 1832. Most of these attempts took place actually outside Spanish soil, but one somewhat successful Wesleyan Methodist experiment in Gibraltar showed the feasibility of a Protestant mission to Spaniards, given the right conditions and opportunities. The lessons learned from all these early attempts encouraged British evangelical societies to enter Spain during the liberal 'period of regencies' from 1833 to 1843 (Chapter'ill). Significantly enough, this was also the first time that political liberalism and constitutional government became firmly established in Spain.

For various reasons, however, evangelical endeavours in that country soon came to an unhappy ending, with the expulsion of practically every Protestant worker. Nevertheless, hopes of resuming these labours were not abandoned. It was, in fact, during the period roughly covering the first decade of Isabella II's reign, that the idea of Spanish evangelization, as conceived by certain evangelical circles in Britain, came into full development. Chapter IV goes into the contemporary factors responsible for this development, and concludes with a brief discussion of the first Protestant missionary society for the specific purpose of converting the Spaniards.

So far, all Protestant efforts in Spain had been ephemeral, and their results uncertain. But by mid-century, advocates of Spanish evangelization had learned from mistakes of the past, and now had a clearer idea of how they might be able to pursue more successfully their objectives. The liberal biennium of 1854-1856 in Spain gave them fresh opportunities to resume their labours (Chapter V). With the Spanish EvangeLization society to coordinate much of the hitherto desultory pattern of Protestant work in that country, more successful results were obtained. Small circles of Spanish evangelicals were gathered, and a so-called 'Reformed Church of Spain' was established, following the ideal of an indigenous movement for religious reform, called the Segunda Reforma (the 'Second Reformation').

The collapse of the liberal biennium, however, inaugurated a new period of conservative reaction in Spain. As Spanish Protestantism was unfortunately closely connected with radical politics, the bitter hatred of Catholic traditionalists towards 'political', philosophical', and 'religious' heterodoxy resulted in the persecution of Spanish Protestants in the early 1860's. Chapter VI discusses this persecution, and the tremendous effect it had in drawing to Spain the attention not only of .British, but also of European Protestantism, as a whole. When- Spanish Protestant leaders were exiled in 1863, evangelical groups in Britain and the continent assisted their labours abroad, in preparation for their eventual return to their own country. It was during this period, particularly from 1863 to 1868, that Reformed or Scottish Presbyterian influence came upon Spanish Protestantism. Ihe 'Reformed Church of Spain', reconstituted in Gibraltar early in 1868, adopted as an expedient a quasi-presbyterian polity, and entered into a relationship of cooperation with the Spanish Evangelization Society. This was a development, which, for good or ill, was to have great significance for the course of Spanish Protestantism and of British evangelical missions to Spain in the next few decades.

She revolution of 1868 and the constitutional declaration of religious liberty the following year opened Spain to the free entry of Protestant missions (Chapter VII). Aside from those evangelical groups, which at one time or another had previously been engaged in missionary labours in Spain, no less than twenty various mission boards, societies, or 'committees of Spanish evangelization' entered that country at this time, 'the novelty of Protestantism and the superficial identification of it with the ideas of the revolution largely accounted for the enthusiastic response to it, on the part of many Spaniards. Although this quickly subsided, Protestantism was able to make significant advances from 1868 to 1874, especially during the first two years of this period (Chapter VIII). More importantly, Protestantism also became an 'accomplished fact' in Spain.

Unfortunately, by the last quarter of the century, Spanish Protestantism came to a period of stagnation, as discussed in Chapter IX. This was largely due to new government restrictions beginning 1876, and the two-pronged opposition by Catholics, on the one hand, and militant atheists, on the other. Moreover, for various reasons, Spanish evangelization had lost much of its original appeal among British Protestants. In Britain, the strongest advocates of this cause belonged to the generation at mid-century. By the 1880's, most of them had passed away, with hardly anyone to take their place. The societies or 'committees of Spanish evangelization' they founded or supported found the work in Spain far too expensive to maintain, for the little results given in return. Moreover, the demands of missions to the heathen now gained the greater attention of British Protestants. Thus, British missionary groups working in Spain reluctantly had to adopt a policy of retrenchment or withdrawal during this period.

The Protestant enterprise in Spain did achieve some measure of success. But on the whole, it fell short of earlier expectations. It was hoped that Protestant!an would somehow provide a third alternative for the Spanish people, between traditional Catholicism, on the one hand, and 'Infidelity', on the other. In this, Protestantism gained little success, partly because the Spaniards found it too cold as a religious alternative, and partly because it had not been able to shed off the stigma of its being an alien importation, of being la cosa de los extranjleros ('the affair of the foreigners'). All these are discussed in the last chapter.

By the beginning of the twentieth century, British Protestants, with a very few exceptions, had cane to realize fully that if Protestantism were to advance in Spain, this had to be accomplished by Spanish converts themselves. Help from abroad was best limited solely to financial assistance. TIhus ended the active role of British evangelical societies in Spanish evangelization. However, it remains as a tribute to them that the roots of present-day Spanish Protestantism can be traced to their efforts in the nineteenth century.